COMPORTAMENTO DE CULTIVARES DE SOJA EM FUNÇÃO DE ÉPOCAS DE SEMEADURA - Gazola, Eduardo; Lemos, Leandro Borges; Farinelli, Rogério; Cavariani, Cláudio (REVISTA DE AGRICULTURA, 2016)
COMPORTAMENTO DE CULTIVARES DE SOJA EM FUNÇÃO DE ÉPOCAS DE SEMEADURA